Identification of dynamic linear models of automotive palm bio-diesel engine for real-time speed control applications - Azuwir, Mohd Nor; Mohd Zaki, Ab. Muin, Prof. Dr.; Abdul Hamid, Adom, Prof. Madya Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/